2020
DOI: 10.1007/s10157-020-01912-w
|View full text |Cite
|
Sign up to set email alerts
|

A higher level of serum furin indicates a higher risk of microalbuminuria: results from a longitudinal study in Chinese adults

Abstract: Background Furin, a key enzyme of natriuretic peptide system, has been suggested to play a role in microalbuminuria, but the association between furin and microalbuminuria has been scarcely studied. Methods Leveraging a longitudinal cohort of Chinese adults who had urinary albumin measured twice 4 years apart, we examined the cross-sectional and prospective associations of baseline serum furin with microalbuminuria, adjusting for age, sex, education level, smoking, drinking, obesity, blood pressure, glucose, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The association between serum furin and the development of diabetes was also found by a prospective cohort study (7). Further, our prior studies found that a lower level of serum furin was also associated with some metabolic dysfunctions related to diabetes, such as obesity (8), hypertension (9), and microalbuminuria (10) in Chinese adults. Moreover, genetic polymorphisms in FURIN, the coding gene of furin protein, have been associated with metabolic syndrome (11) and hypertension (12), both conditions shared many risk factors and mechanisms with diabetes.…”
Section: Introductionsupporting
confidence: 62%
“…The association between serum furin and the development of diabetes was also found by a prospective cohort study (7). Further, our prior studies found that a lower level of serum furin was also associated with some metabolic dysfunctions related to diabetes, such as obesity (8), hypertension (9), and microalbuminuria (10) in Chinese adults. Moreover, genetic polymorphisms in FURIN, the coding gene of furin protein, have been associated with metabolic syndrome (11) and hypertension (12), both conditions shared many risk factors and mechanisms with diabetes.…”
Section: Introductionsupporting
confidence: 62%